Mechanisms Involved in the Beneficial Effects of Spironolactone after Myocardial Infarction - Minicucci, Marcos Ferreira [UNESP]; dos Santos, Priscila P. [UNESP]; Rafacho, Bruna P. M. [UNESP]; Gonçalves, Andrea F. [UNESP]; Silva, Renata A. C. [UNESP]; Chiuso-Minicucci, Fernanda; Gaiolla, Paula Schmidt Azevedo [UNESP]; Polegato, Bertha Furlan [UNESP]; Okoshi, Katashi [UNESP]; Pereira, Elenize J. [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Public Library of Science (PLoS), 2013)
Introduction:Our objective was to analyze the effect of spironolactone on cardiac remodeling after experimental myocardial infarction (MI), assessed by matricellular proteins levels, cardiac collagen amount and distribution, myocardial tissue metalloproteinase inhibitor-1(TIMP-1) concentration, myocyte hypertrophy, left ventricular architecture, and in vitro and in vivo cardiac function.Methods:Wistar rats were assigned to 4 groups: control group, in which animals were submitted to simulated surgery (SHAM group; n=9); group that received spironolactone and in which animals were submitted to simulated surgery (SHAM-S group, n=9); myocardial infarction group, in which animals were submitted to coronary artery ligation (MI group, n=15); and myocardial infarction group with spironolactone supplementation (MI-S group, n=15). The rats were observed for 3 months.Results:The MI group had higher values of left cardiac chambers and mass index and lower relative wall thicknesses compared with the SHAM group. In addition, diastolic and systolic functions were worse in the MI groups. However, spironolactone did not influence any of these variables. The MI-S group had a lower myocardial hydroxyproline concentration and myocyte cross-sectional area compared with the MI group. Myocardial periostin and collagen type III were lower in the MI-S group compared with the MI-group. In addition, TIMP-1 concentration in myocardium was higher in the MI-S group compared with the MI group.Conclusions:The predominant consequence of spironolactone supplementation after MI is related to reductions in collagens, with discrete attenuation of other remodeling variables. Importantly, this effect may be modulated by periostin and TIMP-1 levels. © 2013 Minicucci et al.